Analysis of endosulfan and its metabolites in rat plasma and selected tissue samples by gas chromatography-mass spectrometry - Chan, M.P.L.; Mohd, M.A. (2005)
A method has been developed for the determination of trace levels of alpha-endosulfan, beta-endosulfan, endosulfan sulfate, and endosulfan diol in rat plasma and tissue samples. Endosulfan and its metabolites in the plasma samples were extracted with solid-phase extraction Chromabond-end-capped C18 cartridges and analyzed by a Shimadzu QP-5050A gas chromatograph-mass spectrometer (GCMS) with quadrupole detector in selected-ion-monitoring mode. The analysis of endosulfan and its metabolites in liver and kidney samples involved solvent extraction, Florisil solid-phase-extraction cleanup, and quantitation by GCMS. Recovery experiments for the plasma and tissue samples were conducted over concentration ranges of 10-100 ng mL(-1) and 100-1000 ng mL(-1), respectively. The method was applied to the analysis of trace levels of endosulfan and its metabolites in plasma and tissue samples collected from an animal study. Trace levels of alpha-endosulfan and beta-endosulfan in the ranges of undetectable to 3.11 mug g(-1) and undetectable to 1.19 mug g(-1), respectively, were detected in the kidney samples, whereas trace levels of endosulfan sulfate in the range of 0.02-0.22 mug g(-1) were detected in the liver samples of rats. Neither endosulfan nor its metabolites was detected in any of the plasma samples. (C) 2005 Wiley Periodicals, Inc.